Analisis Decision Table Testing untuk Pengujian Blackbox Website Pusat Studi Bencana IPB - Nasir, Muhammad; Nurjihan, Saniyyah Wafa; Nurbadillah, Nurbadillah; Faturrahman, Nafis; Wiguna, Indra Maki; Lasardi, Ekky Mulia; Wicaksono, Aditya (JATISI, 2024)
This research examines black box testing using the Decision Table Testing technique on the Disaster Study Center website at IPB. This technique was chosen for its ability to identify logical errors and relevant testing scenarios, thereby optimizing test coverage in software development. The research method involves analyzing the website's features to identify potential conditions and actions that serve as the foundation for constructing the decision table. Each condition and action is systematically tested to detect any discrepancies or errors that may arise during website use. The testing results reveal several scenarios that the system has not adequately accommodated, particularly in user input handling and data validation. This finding indicates that the application of Decision Table Testing can improve test quality, especially for features with complex logic. In conclusion, this study highlights the importance of decision table-based testing in enhancing the reliability and accuracy of website functions, making a significant contribution to reducing potential errors that may impact user experience.